Eco-Pedagogy in Inclusive Schools: Food Security as a Foundation for Sustainable Education - Nurhattati; Rihlah Nur Aulia; Ahmad Jauhari Hamid Ripki; Raihan Syarif; Fadhillah (Postgraduate, University of Mataram, 2026)
This study examines how food security can serve as a pedagogical foundation for advancing eco-pedagogy in inclusive elementary education across two contrasting contexts: a nature-based private school and an Islamic elementary madrasa. Using a multi-site qualitative design, it applies participatory ethnographic methods through observations, semi-structured interviews, and school ethnography involving teachers, parents, leaders, and students, including those with special needs. The nature-based school operationalizes eco-pedagogy through hydroponics, organic waste management, and gardening, fostering ecological literacy, collaboration, and shared responsibility. The madrasa frames food security within Islamic commitments to justice, positioning it as both a goal of eco-activism and an expression of religiously grounded social responsibility. Together, these cases show that eco-pedagogy in the Global South extends beyond secular environmentalism and is enriched by faith-based ethics and community practices. The study concludes that embedding food security within inclusive school management broadens eco-pedagogy by situating sustainability education in diverse cultural and religious ecologies, highlighting inclusive schools as effective models of sustainable and socially just education.